Identification and Analyses of Candidate Genes for Rpp4-Mediated Resistance to Asian Soybean Rust in Soybean - Meyer, Jenelle D. F.; Silva, Danielle C. G. [UNESP]; Yang, Chunling; Pedley, Kerry F.; Zhang, Chunquan; van de Mortel, Martijn; Hill, John H.; Shoemaker, Randy C.; Abdelnoor, Ricardo V.; Whitham, Steven A.; Graham, Michelle A. (Amer Soc Plant Biologists, 2009)
Asian soybean rust is a formidable threat to soybean (Glycine max) production in many areas of the world, including the United States. Only five sources of resistance have been identified (Resistance to Phakopsora pachyrhizi1 [Rpp1], Rpp2, Rpp3, Rpp4, and Rpp5). Rpp4 was previously identified in the resistant genotype PI459025B and mapped within 2 centimorgans of Satt288 on soybean chromosome 18 (linkage group G). Using simple sequence repeat markers, we developed a bacterial artificial chromosome contig for the Rpp4 locus in the susceptible cv Williams82 (Wm82). Sequencing within this region identified three Rpp4 candidate disease resistance genes (Rpp4C1-Rpp4C3 [Wm82]) with greatest similarity to the lettuce (Lactuca sativa) RGC2 family of coiled coil-nucleotide binding site-leucine rich repeat disease resistance genes. Constructs containing regions of the Wm82 Rpp4 candidate genes were used for virus-induced gene silencing experiments to silence resistance in PI459025B, confirming that orthologous genes confer resistance. Using primers developed from conserved sequences in the Wm82 Rpp4 candidate genes, we identified five Rpp4 candidate genes (Rpp4C1-Rpp4C5 [PI459025B]) from the resistant genotype. Additional markers developed from the Wm82 Rpp4 bacterial artificial chromosome contig further defined the region containing Rpp4 and eliminated Rpp4C1 (PI459025B) and Rpp4C3 (PI459025B) as candidate genes. Sequencing of reverse transcription-polymerase chain reaction products revealed that Rpp4C4 (PI459025B) was highly expressed in the resistant genotype, while expression of the other candidate genes was nearly undetectable. These data support Rpp4C4 (PI459025B) as the single candidate gene for Rpp4-mediated resistance to Asian soybean rust.